The agile approach as a framework in academic production - Hernández Cruz, Luz María (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The present study responds to an applied investigation in the development of a Thesis Protocol, in which the precepts of agility and the main elements of the Scrum framework were used. Allowing to comply with all the substantive and formal requirements in relation to its contents and, in turn, using tools for specific use for agile management. The results support that the iterative and incremental model of the common practices of the agile approach is adaptable and allow the improvement of the protocol throughout its development. Concluding that Scrum is applicable to the management of academic-scientific projects.